2021
DOI: 10.3390/su132212526
|View full text |Cite
|
Sign up to set email alerts
|

Supply Chains’ Failure in Workers’ Rights with Regards to the SDG Compass: A Doughnut Theory Perspective

Abstract: Many supply chains have pledged to prevent the violation of workers’ rights as part of social sustainability in their far-flung supply chains. This paper provides a way to understand why supply chains fail to overcome the violation of workers’ rights by mapping the UN SDGs onto the social foundations of the doughnut model, with respect to workers’ rights in supply chains. We develop the sustainable supply chain doughnut model with regards to the SDGs, through which we investigate workers’ rights violations. Ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…It supports existing literature of stakeholders' concern about workers' health and safety challenges. For instance, Lotfi et al (2021) found that workers' safety is often neglected in supply efficiency. Alsamawi et al (2017) also provided evidence of hidden workers' challenges along supply chains that have been overlooked.…”
Section: Rq1 What Factors Influence Food Supply Chain Stakeholders To...mentioning
confidence: 99%
“…It supports existing literature of stakeholders' concern about workers' health and safety challenges. For instance, Lotfi et al (2021) found that workers' safety is often neglected in supply efficiency. Alsamawi et al (2017) also provided evidence of hidden workers' challenges along supply chains that have been overlooked.…”
Section: Rq1 What Factors Influence Food Supply Chain Stakeholders To...mentioning
confidence: 99%
“…There are also reports that the world is willing to offset the 'dirty' task to China, in the form of pollution intensive manufacturing, which is readily accepting the burden in exchange of economic growth. Lotfi et al [26], the unsustainable supply chains may be presented in diverse forms including forced labour, child labour, under payment and over-consumption of resources such as water such as in the case of cotton farming.…”
Section: The Link Between Sustainability Transitions and Resource Man...mentioning
confidence: 99%
“…Organizations can gain a competitive edge in emerging markets, so focusing on CSR and corporate social performance is necessary ( Crişan-Mitra et al, 2020 ). Lotfi et al (2021) and Hamid et al (2021) both revealed that many supply chains have the assurance to avoid the abuse of workers’ rights, an essential part of social sustainability in their distant supply chains. They have provided a way to recognize how supply chains do not defeat the infringement of labor’s rights by adopting the UN suggested SDGs on the social basis of the “doughnut model” regarding labor rights in supply chains.…”
Section: Introductionmentioning
confidence: 99%